Buying bestsellers online: A case study in Search & Searchability - Upstill, Trystan; Craswell, Nick; Hawking, David (7th Australasian Document Computing Symposium, 2002)
A website’s design directly aﬀects how well search engines can crawl, match and rank its pages. For this reason, searchability is an important concern in site design. We study the interaction between search engines and Web sites by means of a case study of online bookstores and general-purpose search engines. The task modeled is that of ﬁnding web pages from which a book, described by its title, may be purchased. We ﬁrst compared the relative eﬀectiveness of search engines in ﬁnding pages matching the criterion, regardless of bookstore. Then we compared the relative searchability of the bookstore websites by observing how many times each bookstore contributed useful answers to the search results. Large diﬀerences in the performance of both search engines and bookstores were observed. Two of the search engines performed better than their peers, and one bookstore was far more searchable than all others. To further explore these diﬀerences we tabulate the total number of pages from each bookshop which are included in the search engine indexes. We conclude with recommendations both to bookstores on how they may improve their Web presence, and to search engines on how they may improve their performance for product searches.
://research.microsoft.com/users/nickcr/pubs/upstill_adcs02.pdf